Delirium in an Acute Stroke Setting, Occurrence, and Risk Factors. Issue 11 (November 2019) - Shaw, Robert; Drozdowska, Bogna; Taylor-Rowan, Martin; Elliott, Emma; Cuthbertson, Gillian; Stott, David J.; Quinn, Terence J.
Abstract : Background and Purpose—: Delirium is a common and serious complication of acute illness. We describe delirium occurrence in an unselected, acute stroke population. Methods—: We collected data from consecutive stroke admissions. We performed comprehensive cognitive assessment within the first week including Diagnostic Statistical Manual-5–based delirium diagnosis. We reported proportion with delirium and the clinical and demographic associations with delirium using multiple logistic regression. Results—: Of 708 patients, median age of 71 years (interquartile range, 59–80), we recorded delirium in 187 of 708 (26.4%; 95% CI, 23.0–30.0). Across 395 patients with complete risk factor data (105 delirium), factors independently associated with delirium were: age (odds ratio, 1.05; 95% CI, 1.03–1.08), drug/alcohol misuse (odds ratio, 2.64; 95% CI, 1.10–6.26), and stroke severity (odds ratio, 1.22; 95% CI, 1.14–1.31). Conclusions—: Delirium is common in acute stroke, affecting 1 in 4. It may be possible to predict those at risk using prestroke and stroke-specific factors. Clinical Trial Registration—: URL: researchregistry.com . Protocol: 1147. Abstract : Supplemental Digital Content is available in the text.